Clinical Outcome of Hypertensive Uveitis - Deborah Lewkowicz; François Willermain; Lia Judice Relvas; Dorine Makhoul; Sarah Janssens; Xavier Janssens; Laure Caspers (Journal of Ophthalmology)
Purpose. To review the clinical outcome of patients with hypertensive uveitis. Methods. Retrospective review of uveitis patients with elevated intraocular pressure (IOP) > 25 mmHg and >1-year follow-up. Data are uveitis type, etiology, viral (VU) and nonviral uveitis (NVU), IOP, and medical and/or surgical treatment. Results. In 61 patients, IOP values are first 32.9 mmHg (SD: 9.0), highest 36.6 mmHg (SD: 9.9), 3 months after the first episode 19.54 mmHg (SD: 9.16), and end of follow-up 15.5 mmHg (SD: 6.24). Patients with VU (n=25) were older (50.6 y/35.7 y, p=0.014) and had more unilateral disease (100%/72.22%  p=0.004) than those with NVU (n=36). Thirty patients (49.2%) had an elevated IOP before topical corticosteroid treatment. Patients with viral uveitis might have higher first elevated IOP (36.0/27.5 mmHg, p=0,008) and maximal IOP (40.28/34.06 mmHg, p=0.0148) but this was not significant when limited to the measurements before the use of topical corticosteroids (p=0.260 and 0.160). Glaucoma occurred in 15 patients (24.59%) and was suspected in 11 (18.03%) without difference in viral and nonviral groups (p=0.774). Conclusion. Patients with VU were older and had more unilateral hypertensive uveitis. Glaucoma frequently complicates hypertensive uveitis. Half of the patients had an elevated IOP before topical corticosteroid treatment.